A very rare case of primary meningococcal arthritis in an adult male. Issue 2 (6th October 2014) - Nihonyanagi, Shin; Sunakawa, Keisuke; Cui, Longzhu; Masaki, Tsuguto; Wada, Tatsuhiko; Hoshiyama, Takayuki; Nakamura, Masaki; Takayama, Yoko; Kanoh, Yuhsaku; Ogawa, Akifumi; Shichiri, Masayoshi; Hanaki, Hideaki
Key Clinical Message We report here a very rare case of primary meningococcal arthritis of the knee joint without clinical features associated with meningococcemia, meningitis, or meningococcal complications. The patient suffered from diabetes mellitus and had experienced two episodes of joint trauma. Intravenous infusion of ampicillin/sulbactam for 18 consecutive days was successful.